Au-TiO2 nanoparticles exposure induced oxidative stress and neurotoxicity in rat. (3rd April 2021) - Mezni, Ali; Khazri, Abdelhafidh; Khazri, Hassen; Mezni, Amine; Maalaoui, Aziza; Touyalia, Samir; Balti, Rafik; Dellali, Mohamed; Mahmoudi, Ezzeddine; Beyrem, Hamouda
Abstract: Context: The Au-TiO2 NPs have a wide range of applications and can easily enter the cells. Due to their properties, they can cause toxicity. Objective: It was aimed to test the toxic effects of Au-TiO2 NPs in the brain, heart, kidney and liver of rats in this work. Materials and methods: All used rats in this work were treated using diverse concentrations (doses) of NPs (100 and 200 mg/kg bw) for 21 days. SOD, CAT, AChE activities and MDA, H2 O2, NO contents were evaluated in different organs. Results: The Au-TiO2 NPs exposure induced biochemical changes in different organs of rats in view of oxidative stress and neurotoxicity by the alteration of the activity of the enzyme of neurotransmitter (AChE activity). Conclusion: The Au-TiO2 NPs have the potential to interact with rat's biochemical status and cause undesirable effects. One of those damaging effects was oxidative stress and neurotoxicity. Clinical significance: The study signifies the impact of usage of Au-TiO2 NPs in the medical field for further exploration.